Quantification of rifaximin in tablets by an environmentally friendly visible spectrophotometric method - Brbaklic, Vesna; Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Elsevier, 2017)
Introduction: Rifaximin is an antibiotic with a wide spectrum of antibacterial activity. Due to its non-absorbable nature and mechanism of action, it is commonly used for treating travelers’ diarrhea. It still does not have standardized methods in most official compendiums. This paper aimed to validate an environmentally friendly spectrophotometric method in the visible region for quantification of rifaximin in tablets. Method: Validation was performed in terms of International Conference on Harmonization guidelines, examining linearity, precision, selectivity, specificity, accuracy and robustness. The method considered rifaximin solutions in purified water and ethyl alcohol (5:1, v/v) at a wavelength of 477 nm. Conclusion: The method showed great linearity in the concentration range between 15 and 50 µg L-1 with correlation coefficient higher than 0.9998. Selectivity was determined by submitting the rifaximin in tablets to the forced degradation in ultraviolet light and acidic, basic, oxidative, neutral solution. The interday and intraday precision presented deviations of less than 1 %. The accuracy was 99.12 %. The method was robust to the variation in wavelength and source of purified water. The validated method proved to be fast, cost effective and suitable for routine quality control of rifaximin in tablets, avoiding the use of polluting reagents.
Keywords: Environmentally friendly; Method validation; Rifaximin; Spectrophotometry in the visible region; Tablets